2019
DOI: 10.2134/agronj2018.10.0693
|View full text |Cite
|
Sign up to set email alerts
|

Greater Biomass Accumulation at Anthesis Increases Nitrogen Use Efficiency in Winter Wheat

Abstract: Soft red winter wheat (Triticum aestivum L.) production relies on efficient nitrogen (N) fertilization to maximize grower profitability and mitigate environmental impacts. Therefore, a panel of 11 elite wheat lines were grown as a randomized complete block design in four environments under low (LN) and high (HN) N rates to: (i) assess the genotypic variation in aboveground biomass (AGBM) and N yield (AGNY) throughout the growing season; and (ii) investigate the associations between yield and N‐related traits w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 67 publications
2
8
0
Order By: Relevance
“…This was not the case for aboveground N yield in the present study where the significant interactions between genotype and testing environment supported the need for testing in diverse environments. This result was not observed in a recent study of grain faba bean sampled at harvest maturity (Allito et al, 2020), but similar findings have been reported in other grain and cover crop species at the flowering stage including winter wheat (Triticum aestivum L.) (Brasier et al, 2019) and common bean (Phaseolus vulgaris L.) (Barbosa et al, 2018). Surprisingly, Ndfa was only significantly affected by testing environment in the present study, whereas previous investigations reported significant genotypic variation for this trait in small faba bean panels (Duc et al, 1988;Nebiyu et al, 2014).…”
Section: ) Recent Grain Faba Bean Breeding Efforts In the Pacificsupporting
confidence: 83%
“…This was not the case for aboveground N yield in the present study where the significant interactions between genotype and testing environment supported the need for testing in diverse environments. This result was not observed in a recent study of grain faba bean sampled at harvest maturity (Allito et al, 2020), but similar findings have been reported in other grain and cover crop species at the flowering stage including winter wheat (Triticum aestivum L.) (Brasier et al, 2019) and common bean (Phaseolus vulgaris L.) (Barbosa et al, 2018). Surprisingly, Ndfa was only significantly affected by testing environment in the present study, whereas previous investigations reported significant genotypic variation for this trait in small faba bean panels (Duc et al, 1988;Nebiyu et al, 2014).…”
Section: ) Recent Grain Faba Bean Breeding Efforts In the Pacificsupporting
confidence: 83%
“…At the reduced N rate, NUpE was 107% compared to 80-81% for the three full-rate N treatments, indicating that when fertilizer N rates are low, the plant is more efficient in utilizing fertilizer N and soil N reserves (Table 3). This is commonly reported in the literature (Brasier et al, 2019). Similar to total N uptake, there were no differences in NUpE between the standard N treatment and the ESN blend or the split N application treatments.…”
Section: Nitrogen and Plant Growth Regulator Managementsupporting
confidence: 86%
“…Brasier et al. (2019) reported a significant positive correlation ( r = .63) between DTA and NUpE in winter wheat. This may have been the case at the Carman19, however, in our study, when combined across all site‐years and treatments there was a significant negative correlation between NUpE and DTA ( r = –.36) (Table 5).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Selection based on physiological traits associated with N response may increase genetic gains through more targeted breeding (Gaju et al, 2011). Building on this application of physiology theory, recent investigations of NUE in winter wheat have identified significant trait associations with NUE across N rates including NUtE (Cormier et al, 2013) and aboveground biomass (Brasier et al 2019;Hitz et al, 2017). Similar findings were observed in the present study, where aboveground biomass at maturity was significantly associated with grain yield when 67 kg N ha −1 was applied in Study II and both N rates were applied in Study III.…”
Section: Traits Underlying Variation In Nuementioning
confidence: 99%